Modifying Positional Selectivity in C–H Functionalization Reactions with Nitrogen-Centered Radicals: Generalizable Approaches to 1,6-Hydrogen-Atom Transfer Processes - Short, Melanie A.; Blackburn, J. Miles; Roizen, Jennifer L. (Synlett, 2020)
Nitrogen-centered radicals are powerful reaction intermediates owing in part to their ability to guide position-selective C(sp3)–H functionalization reactions. Typically, these reactive species dictate the site of functionalization by preferentially engaging in 1,5-hydrogen-atom transfer (1,5-HAT) processes. Broadly relevant approaches to alter the site-selectivity of HAT pathways would be valuable because they could be paired with a variety of tactics to install diverse functional groups. Yet, until recently, there have been no generalizable strategies to modify the position-selectivity observed in these HAT processes. This Synpacts article reviews transformations in which nitrogen-centered radicals preferentially react through 1,6-HAT pathways. Specific attention will be focused on strategies that employ alcohol- and amine-anchored sulfamate esters and sulfamides as templates to achieve otherwise rare γ-selective functionalization reactions.1 Introduction2 Transformations that Rely on Structural Constraints or Weakened C–H Bonds to Favor 1,6-HAT Processes3 Sulfamate Esters Engage Selective 1,6-HAT Processes4 Expansion to 1,6-HAT Processes with Masked Amine Substrates5 Conclusions and Outlook
Keywords: hydrogen-atom transfer; remote C–H functionalization; radicals; nitrogen-centered radicals; sulfamate ester; sulfamide